Incidence and Patterns of Congenital Heart Disease Among Jordanian Infants, a Cohort Study From a University Tertiary Center - Khasawneh, Wasim; Hakim, Fakhri; Abu Ras, Omayma; Hejazi, Yara; Abu-Aqoulah, Abdullah (Frontiers in Pediatrics, 2020)
Background: Data is limited about the incidence of congenital heart disease in Jordan. The goal of this study is to determine the incidence and patterns of congenital heart diseases (CHD) among Jordanian infants evaluated at King Abdullah University Hospital. Methods: A retrospective chart review was conducted for all infants who had an echocardiogram evaluation in the 3-year period July 2016-June 2019. All included infants had a 2-dimentional echocardiogram with a Doppler vascular study performed by the same cardiologist. Infants with a structural congenital heart disease were included in the analysis. Results: A total of 1028 infants were evaluated at the cardiology department during the study period. 865 had an abnormal echo finding. 298 were diagnosed with CHD. The incidence of CHD was 25 per 1000 live births. 51% were premature infants. The majority of cases were mild CHD. Patent ductus arteriosus was the most common acyanotic lesion followed by ventricular septal defect and atrial septal defect with a prevalence of 44%, 25% and 25% respectively. Cyanotic CHD constituted 6% of all CHD. Tetralogy of Fallott was the most common cyanotic CHD. The main indication for referral was hearing a heart murmur during physical examination. Conclusion: Although the incidence of CHD in our cohort was relatively high, the majority of cases were acyanotic mild CHD with favorable prognosis. A wider population-based study is needed to evaluate the incidence and better understand the patterns and distribution of CHD at a national level.